Narrative review of application of metagenomic approaches to study the link between oropharyngeal microbiome and infectious diseases - Diallo, Kanny; Missa, Kouassi Firmin; Tuo, Jeremie Kolotioloman; Amoikon, Tiemele Laurent Simon; Bla, Brice K.; Bonfoh, Bassirou (Frontiers in Microbiology, 2023)
Context: Viral and bacterial infections are major causes of morbidity and mortality worldwide.The oropharyngeal microbiome could play an important role in preventing invasion of viral and bacterial pathogens by modulating its content and the host's innate immune response. Next Generation Sequencing (NGS) technologies now enable in-depth study of the genomes of microbial communities. The objective of this review is to highlight how metagenomics has contributed to establish links between changes in the oropharyngeal microbiome and emergence of bacterial and viral diseases.Method: Two search engines, PubMed and Google scholar were used with filters to focus searches on peer-reviewed original articles published between January 2010 and September 2022. Different keywords were used and only articles with metagenomic approaches were included.Results: This review shows that there were few articles studying the link between oropharyngeal microbiome and infectious diseases. Studies on viruses using metagenomic techniques have been growing exponentially in recent years due to the Covid-19 pandemic. This review shows that most studies still focus on the basic identification of microorganisms in different disease states and multiple microorganisms (Alloprevotella, Prevotella, Bacteroides, Haemophilus, Streptococcus, Klebsiella sp., Acinetobacter sp…), have been associated with development of infections such as childhood wheezing, influenza, Covid-19, pneumonia, meningitis, and tuberculosis.The oropharyngeal microbiome, despite its importance, remains poorly studied.A limited number of articles were identified but this number has increased exponentially since 2020 due to research conducted on Covid-19. These studies have shown that metagenomic has contributed to the unbiased identification of bacteria that could be used as biomarkers of various diseases and that further research is now needed to capitalise on those findings for human health benefit.